2006
DOI: 10.1038/sj.gt.3302826
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackie adenovirus receptor and ανβ3/ανβ5 integrins in adenovirus gene transfer of rat cochlea

Abstract: This study was designed to determine whether Coxsackie adenovirus receptor (CAR) and anb3/anb5 integrin co-receptors are involved in adenovirus gene transfer in the rat cochlea. We find that CAR and integrin co-receptors are expressed in every cell subtype transduced by the adenoviral vector Ad5 DE1-E3/cytomegalovirus/green fluorescent protein (GFP) on cochlear slices in vitro. The spiral ganglion neurons, which do not express CAR, were not transduced by the virus. Blocking these receptors by monoclonal antibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 30 publications
(24 reference statements)
3
28
0
Order By: Relevance
“…37,38 Our demonstration of adenoviral transfection in human sensory epithelia suggests CAR receptors are present in the mature human inner ear and supports the development of adenovirus, or other vectors that bind the CAR receptor, for future human application.…”
Section: Cell Viability and Availabilitymentioning
confidence: 54%
“…37,38 Our demonstration of adenoviral transfection in human sensory epithelia suggests CAR receptors are present in the mature human inner ear and supports the development of adenovirus, or other vectors that bind the CAR receptor, for future human application.…”
Section: Cell Viability and Availabilitymentioning
confidence: 54%
“…CAR is present in cells of the auditory epithelium but its distribution does not completely explain the pattern of cellular transduction in this epithelium, during development and in the mature tissue [28, 29]. Lack of transgene expression in hair cells is especially intriguing, considering the presence of CAR in these cells.…”
Section: Characteristics Of Adenoviral Gene Transduction In the Innermentioning
confidence: 99%
“…Anatomical barriers are present that alter CAR's accessibility to adenovirus. Adenoviruses do not pass through the perilymph-endolymph barrier, as has previously been shown in guinea pigs [35] . After attaching the host cells by binding to CAR, adenovirus is internalized through integrins ␣ ␤ 3 or ␣ ␤ 5 [38,39] .…”
Section: Receptors and Affinity To The Inner Earmentioning
confidence: 67%
“…Both of them are essential for adenovirus infection. Venail et al [35] reported that antibody against integrins-␣ did not abolish or even had no influence on adenovirus infection. There, results can only be explained by a noneffective blockage of integrin pathway.…”
Section: Receptors and Affinity To The Inner Earmentioning
confidence: 99%
See 1 more Smart Citation